ANALISA KONTRIBUSI PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH PROVINSI DKI JAKARTA - Riftiasari, Dinar (Yayasan Akrab Pekanbaru, 2018)
The purpose of this research is to find out the contribution of local tax and local retribution to the local own-source revenue at province DKI Jakarta. Qualitative research method is used as the research method and the data collection method is performed by conducting literary study and field study which consist of observation, documentation and interview. This study variables include local taxes , levies and revenue. Based on the result of research it has been found that the local tax gives a very big contribution to the local own-source revenue with its contribution average percentage is 84,74% and the local retribution gives a very small contribution to the local own-source revenue with its contribution average percentage is 2,86%. Keywords: Local Tax, Local Retribution, Local Own-Source Revenue